Optimizing planting dates and irrigation schedules to enhance wheat production in Fars Province under future climate scenarios using the CERES-Wheat model - Ebrahimi, Farkhondeh; Edalat, Mohsen; Naderi, Ruhollah (PeerJ, 2025)
Background Climate change poses significant threats to wheat production, particularly in regions prone to increasing temperatures and water scarcity. This study aimed to explore the optimum planting date and irrigation schedule that increases winter wheat productivity under the potential adverse impacts of climate change. Methods A combination of data from 2-year field experiments (2018–2019 and 2019–2020) and simulation data of the Crop Environment Resource Synthesis (CERES)-Wheat model was employed in this research. The weather data emanating from eight global climate models (GCMs) of Climate Model Intercomparison Project 5 and 6 (CMIP5 and CMIP6) under Representative Concentration Pathways (RCP-4.5 and RCP-8.5) and Shared Socioeconomic Pathways (SSP-245 and SSP-585) were used to predict rainfall and temperature variations in two future periods (2041–2070 and 2071–2100). Results The findings demonstrated that the annual maximum and minimum temperatures (T(max) and T(min)) would respectively increase by 3.14 °C and 3.50 °C in the 2050s, based on averaging all models of CMIP5 and CMIP6 with the highest T(max) values projected for June to August. In the 2080s, further warming of 4.54 °C and 4.66 °C was anticipated in the annual T(min) and T(max), again peaking in June to August, respectively. As opposed to the baseline period, precipitation over the growing season (October to May) is projected to be reduced by 23.03% and 29.48% in the 2050s and 2080s, respectively, with the lowest rainfall occurring in May. The anthesis date was projected to decline by 27, 37, 17, and 31 days under RCP-4.5, RCP-8.5, SSP-245, and SSP-585 scenarios, respectively. Additionally, the findings indicated that the period in which the wheat is grown decreased by 23, 32, 22, and 29 days under RCP-4.5, RCP-8.5, SSP-245, and SSP-585, respectively. Planting wheat from October 22 to November 11 recorded the highest value of grain yield in all irrigation treatments. On average, across all scenarios, with a 3-week early planting date compared to October 22, the grain yield was predicted to decrease by 22–44%. Therefore, adjusting the planting date and the irrigation time as the adaptation strategy during climate change slightly increased wheat grain yield in semi-desert regions like the Fars province. This advancement is linked to the crop’s ability to utilize cooler temperatures during critical growth phases when sown earlier.
Keywords: CERES-Wheat model; Climate change; CMIP5; CMIP6; Adaptation strategy